The Influence of Leadership, Work Discipline, and Motivation on Employee Performance with Religiosity as a Moderating Variable - Isnaini Harahap; Nur Ahmadi Bi Rahmani; Ahmad Mu'arif Pohan; Muhammad Munawir Pohan (Almana : Jurnal Manajemen dan Bisnis, 2023)
Organizations and corporations cannot function without their human resources to ensure that a company's management and operations are effective. With religion serving as a moderator, this study aimed to investigate how leadership, work ethic, and motivation affect employee performance. A causal-correlational strategy was used in this quantitative study. Eighty-eight people were selected as the sample size. Information for this study comes from both primary and secondary sources. A survey using a Likert scale was used as the data collection tool. A multiple linear regression analysis was used to analyze the data. The results showed no correlation between leadership and employee performance that was either favorable or statistically significant. Employee performance is positively and significantly impacted by workplace discipline. Performance and employee motivation are positively and significantly correlated. Employee performance and moderate religion do not positively and significantly relate. Workplace discipline and employee performance are not completely connected considerably with religiosity. There is no significant correlation between employee performance influenced by religion and job discipline.